The Ottawa panel clinical practice guidelines for the management of knee osteoarthritis. Part three: aerobic exercise programs - Brosseau, Lucie; Taki, Jade; Desjardins, Brigit; Thevenot, Odette; Fransen, Marlene; Wells, George A; Mizusaki Imoto, Aline; Toupin-April, Karine; Westby, Marie; Álvarez Gallardo, Inmaculada C; Gifford, Wendy; Laferrière, Lucie; et al. (Clinical rehabilitation, 2017)
To identify effective aerobic exercise programs and provide clinicians and patients with updated, high-quality recommendations concerning traditional land-based exercises for knee osteoarthritis. A systematic search and adapted selection criteria included comparative controlled trials with strengthening exercise programs for patients with knee osteoarthritis. A panel of experts reached consensus on the recommendations using a Delphi survey. A hierarchical alphabetical grading system (A, B, C+, C, D, D+, or D-) was used, based on statistical significance ( P < 0.5) and clinical importance (⩾15% improvement). The five high-quality studies included demonstrated that various aerobic training exercises are generally effective for improving knee osteoarthritis within a 12-week period. An aerobic exercise program demonstrated significant improvement for pain relief (Grade B), physical function (Grade B) and quality of life (Grade C+). Aerobic exercise in combination with strengthening exercises showed significant improvement for pain relief (3 Grade A) and physical function (2 Grade A, 2 Grade B). A short-term aerobic exercise program with/without muscle strengthening exercises is promising for reducing pain, improving physical function and quality of life for individuals with knee osteoarthritis.